A 60-Year-Old Female With Metastatic Malignant Melanoma of the Scalp Responding to Ipilimumab. (9th March 2018) - Lohrenz, Sarah; Crawford, Jennifer; Souf, Shawki
Melanoma is an aggressive disease that accounts for approximately 75% of skin cancer-related deaths. In the past, treatment options for patients with advanced stage melanoma have been limited with poor response rate and failure to improve overall survival (OS). Immunotherapy is a promising treatment that has been shown to improve OS and in cases produce durable remissions—a novel concept in the treatment of advanced melanoma. We report a case of advanced stage metastatic malignant melanoma of the scalp with a durable (31 months) response to ipilimumab immunotherapy. This is the first case study reporting long-term, progression-free response to ipilimumab in metastatic melanoma without side effects of therapy. This case adds to the evidence supporting early referral and initiation of ipilimumab in patients who can tolerate it, with the goal of producing a sustained treatment-free response and preserved quality of life.